Impact of Crude Oil discharge from Oil Refineries near Gwer Road of Erbil City on Soil Physico-chemical Properties and Metal Emancipations - Darya K. Mirza; Ismaeel T. Ahmed (Zanco Journal of Pure and Applied Sciences, 2023)
The study was carried out in October 2021 nearby oil refineries which are located near Gwer road and 15 km far away from Erbil city (36° 8'32.31"N, 43°46'32.61"E), to investigate the impact of residual crude oil discharged from surrounding oil refineries on soil Physico-chemical properties and heavy metals contamination. A total of 108 soil samples were collected from (8) different locations, (4) distances, and (3) depths alongside the residual crude oil stream. By using (XRF) technique to determine total heavy metals concentration from collected soil samples. The range of soil pH is between (7.23- 8.7) and an increase in crude oil quantity causes increases in soil pH. (Fe) has the highest concentration among the studied metals ranging between (11925.09 - 22394.37 mgkg-1) followed by (Mn) which ranged between (127.89 - 528.12 mgkg-1) and (Zn) ranged between (41.68 - 107.58 mgkg-1). According to Pearson’s correlation, there is a significant positive correlation between (Fe and Mn) at (p ≤ 0.01, r=.753**) which indicates both metals are derived from the same source. Moreover, there are a significant positive correlation between (Zn and Mn) at (p ≤ 0.05, r=.338*) However, the correlation is less strong compared to (Fe and Mn) this mean (Zn) derived from multiple sources other than crude oil like automobile and truck tire which is one of the major sources for (Zn), since the study area was located next to the busy road.